Brilliance [compact disc, unabridged] - Sakey, Marcus (Sakey, Marcus. Brilliance saga, 2013)
A little girl reads people's darkest secrets by body language. A man who sees patterns in the stock market racks up billions. A woman can go invisible by being where no one is looking. They're called "brilliants," and Nick Cooper is one of them; a federal agent, Cooper's gifts make him exceptional at hunting terrorists. His latest target is a dangerous brilliant intent on provoking civil war. To catch him, Cooper will have to violate everything he believes in-and betray his own kind.